The Palm Beach murders : thrillers - Patterson, James, 1947-; Born, James O.; Arnold, Tim, (Journalist); Swierczynski, Duane (Grand Central Publishing, 2021)
Three stories from the world's best-selling author include the tale of a pair of divorcees who begin a strangely intense game of make-believe and a popular advertising exec who notices the people around him are being murdered.